2019
DOI: 10.3389/feart.2019.00017
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Production of H2 and Magnetite From Steel Slags: A Geo-Inspired Approach Based on Olivine Serpentinization

Abstract: The interaction between ultramafic rocks and hot seawater at slow-spreading mid-oceanic ridges triggers hydrothermal redox reactions which are known to produce magnetite and H 2 under appropriate pressure and temperature conditions. Steel slags share some common properties with ultramafic rocks. They are composed of anhydrous and refractory minerals formed at temperatures exceeding 1,200 • C and they contain ferrous iron in comparable amounts. Consequently, when submitted to hydrothermal conditions both types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 108 publications
0
15
0
Order By: Relevance
“…However, the overall assessment and the kinetic of this redox equation (roughly 3[FeO] + H 2 O => Fe 3 O 4 + H 2 ) remain also poorly known. They appear to be strongly dependent on the temperature but also on the presence of catalyzers [17]. Nevertheless, the Iron oxidation is the more probable source of many of the observed H 2 onshore emanations, it is largely present associated with Silicon and Magnesium within the olivine and orthopyroxene in the oceanic crusts.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…However, the overall assessment and the kinetic of this redox equation (roughly 3[FeO] + H 2 O => Fe 3 O 4 + H 2 ) remain also poorly known. They appear to be strongly dependent on the temperature but also on the presence of catalyzers [17]. Nevertheless, the Iron oxidation is the more probable source of many of the observed H 2 onshore emanations, it is largely present associated with Silicon and Magnesium within the olivine and orthopyroxene in the oceanic crusts.…”
mentioning
confidence: 97%
“…We consider that the O_1 is the more probable, it means that the H 2 may come from water/rock interactions in the crust. Knowing the kinetics of these reactions will be key for the H 2 production since we are talking about a flow and not about fossil resources; research is active in that domain [17]. Nevertheless, we will leave the question of origin and flow rate open, they are not the topic of this article, and discuss the favorable geological settings and the surface evidences which indicate that a H 2 generation could be currently active in a given area.…”
mentioning
confidence: 99%
“…As for "Fe-bearing" phases, oxidation of Fe(II) in magnetite and of Ni or reduced sulfur in Ni-bearing phases such as alloys or sulfides may intrinsically produce more H 2 without a true catalytic effect occurring. Indeed, moderate amounts of Ni metal particles have recently been identified as catalysts of FeO oxidation under hydrothermal conditions (Michiels et al, 2018) and this effect may be extrapolated to Fe-bearing minerals such as olivine (Brunet, 2019). Conversely, H 2 concentrations in spinel-bearing experiments cover the whole range of concentrations despite run duration or P-T conditions (all communities) and always lie below the maximum values observed, which explains the negative correlation observed in Figure 4.…”
Section: Effect Of Accessory Solid Phasesmentioning
confidence: 85%
“…The dataset can also be extended to other reactions under similar conditions using different solid reactants, such as mine-tailing products, to produce H 2 , CH 4 and other carbon species (e.g. Kularatne et al, 2018;Michiels et al, 2018;Brunet, 2019). We hope that this dataset and the analysis by Barbier et al (2020) stimulate complementary experiments that could fill the identified gaps; this would allow editing future versions of this dataset in a few years and potentially help people better understand the fate of carbon under highly reducing conditions such as the one produced during serpentinization.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%